PENANGANAN TINDAK PIDANA PENGGELAPAN DANA PERUSAHAAN BERDASARKAN PASAL 374 KUHP DI POLRES KOTA SAMARINDA - Herlinawati Purba (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
AbstractCrime as a social phenomenon that occurs on earth may never end. Crime is a complex phenomenon that can be understood from many different sides. That is why in everyday life we can see various comments about a crime that is different from one another.Embezzlement is included in the section of crimes regulated in the Criminal Code (book two) Articles 372-374. Embezzlement is a type of crime against property. Crimes that occur in social life are a phenomenon that continues to be in the spotlight. Talking about the emergence of embezzlement, it cannot be separated from the causes of the evil itself. Keywords: Crime. Embezzlement